NK Cells Can Target Castration-resistant Prostate Cancer Stem Cells With the Involvement of Degranulation Pathway - HATTORI, ASUKA; SEKI, TAIGA; KATO, KAZUNORI; VIRGONA, NANTIGA; MIYAKOSHI, YUICHI; KOHNO, KAKERU; YANO, TOMOHIRO (Anticancer research, 2025)
Castration-resistant prostate cancer (CRPC) is lethal and refractory to therapy. To reduce the risk of CRPC, a direct elimination strategy of cancer stem cells is needed, but a promising approach to target cancer stem cells has not yet been established. Natural killer (NK) cells are known to exhibit potent cytotoxic activity against cancer stem cells. In this study, we aimed to clarify whether CRPC cells with stemness characteristics are more sensitive to NK cells than CRPC cells without stemness features. PC-3 stem-like (PC3-stem) cells separated from the CRPC cell line PC-3 (PC3) using a three-dimensional tumor sphere culture method. Each type of tumor cells (PC3 or PC3-stem) were then co-cultured with the human NK-like cell line KHYG-1, and cell viability was determined using the WST-8 method and crystal violet staining. mRNA levels were determined using real-time PCR, and the expression of each protein was evaluated using flow cytometry and ELISA. KHYG-1 cells exhibited more potent cytotoxicity against PC3-stem cells than PC3 cells. In addition, the mechanism that leads to the NK cell cytotoxicity favoring toward PC3-stem cells was associated with the NKG2D-MICA/B-mediated degranulation pathway. These observations raise the possibility that targeting CRPC stem cells with NK cells may lead to the establishment of novel therapeutic strategies for the suppression of CRPC development.